Mineral nutrition, planting density, biometric and phenological characterization of the lamb´s ear - Silva, Luis Felipe Lima e; Souza, Douglas Correa de; Resende, Luciane Vilela; Gonçalves, Wilson Magela; Costa, Gabriele Mikami; Martins, Inara Alves (MAGISTRA, 2018)
Abstract: The lamb’s ear (Stachys byzantina K. Koch) is an example of underutilized food species, characterized in Brazil as an unconventional vegetable. Currently, there is enough government incentive for the rescue and reintroduction of this species in the Brazilian food, however, there is little information available about the suitable techniques for its cultivation and for large-scale production. Thereon, we aimed to evaluate the lamb’s ear plants development under different levels of fertilization, supplied by NPK formulations determined by variations obtained from adjustments to the recommendations for fertilization of leafy crops, besides evaluating the behavior of the crop, when conducted at different planting densities, as well as to determining the characterization of the phenological stages of this species in the region southern Minas Gerais. Two experiments were conducted, one to determine the phenological stage, which was arranged in a design of randomized blocks with four replications, and the other for evaluation of the phytotechnical handling of the crop, which was arranged in the randomized blocks with split plots. The production rate varied significantly when the crop was subjected to different levels of fertilizer and different spacing, and the best result was 48.05 Mg.ha-1 by handling in a less dense spacing of 50 cm between plants and 30 cm between lines under the fertilization of 300 kg.ha-1 N, 240 kg.ha-1 of K2O and 800 kg.ha-1 P2O5. The crop cycle, from planting to harvest, was set at 140 days after the planting. Keywords: Unconventional vegetables, Crop cycles, Stachys byzantina K. Koch.